Avascular osteonecrosis in a young patient with a novel coronavirus infection - T. V. Kirsanova; A. D. Meshkov; T. M. Manevich; M. А. Lysenko (Спортивная медицина: наука и практика, 2022)
COVID‑19 continues demonstrating possible complications after recovery. One of these complications is avascular osteonecrosis, which can lead to bone destruction and patient disability. Cases of the development of osteonecrosis associated with coronavirus infection were widely reported during and after the SARS epidemic in 2003. They also appear to be common in COVID‑19 infection. All patients who have recovered from COVID‑19 infection, especially who received glucocorticoids, are threaten of osteonecrosis development.We describe a case of bone necrosis in a healthy young woman without additional risk factors with a mild course of COVID, who received a short course of glucocorticoids.This is the first described case of COVID‑induced osteonecrosis in our country, although due to the large‑scale use of glucocorticoids, there are probably more such cases. Early diagnosis is important to prevent disease progression. Therefore, clinical alertness is necessary in all patients with COVID‑19.